Profile of Creative Thinking Skills Students in One of Public Junior High School in Surakarta - Hafsah Salsabila (Program Studi Pendidikan Biologi, FKIP Unpas, 2018)
This study aims to determine the creativity students in one of the State Junior High School (JHS) in Surakarta. The method used in this research is descriptive method. The population in this study is all students of class VII and VIII SMP. The sampling technique uses stratified random sampling with the number of samples are 50 students. Creative thinking skills using written tests which developed by Dian Purnaman Sari (2017). Creative indicators consisting of fluency, flexibility, authenticity and detail. Data analysis techniques use descriptive statistics. The results showed that the level creativity of student in creative enough category, with level of fluency: 1,4, flexibility: 1, authenticity: 1,6, and detail: 1.